Pemecahan Masalah dan Solusi Terhadap Perilaku Dewasa Madya dalam Pemeliharaan Lingkungan dan Alam - Desi Wulandari Siahaan; Elsaday MS; Bella Sinambela; Damayanti Nababan (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2022)
Abstract. Environment is everything that affects human growthand animals. While the environment is everything that being around living things (organisms) that have reciprocal effects on living things. Effort environmental preservation means maintaining the existence of the environment forever, everlasting and unchanging. By doing actions arbitrarily to the environment by exploiting regardless of the consequences, clearly contrary to Christian teachings Instability of natural conditions, disasters and calamities that occur in nature, because it is caused by human hands. Management This environment aims to achieve harmonious relations between humans and the environment. inner harmony Christian teachings include four things, namely: harmony with God, harmony with society, harmony with the natural environment and harmony with oneself. Efforts to preserve the environment alive, this received serious attention from the shepherd. written in the bible about reviving dead land, planting trees (reforestation) and the contents of the bible about the prohibition of open defecation. Messages written in God's word, are awakening to his people to always increase awareness of the environment.